2018
DOI: 10.1007/s13762-018-1720-0
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-induced oxidative stress-mediated change in fatty acids composition of cyanobacterium Synechococcus sp. PCC7942

Abstract: The present study was undertaken to examine the salinity stress-induced physiological and biochemical alterations in the cyanobacterium Synechococcus sp. PCC 7942. Cyanobacterial cultures supplemented with different concentrations of NaCl were evaluated for growth, carbohydrate, total lipid, ROS generation, and stress biomarkers to evaluate the ROS-mediated lipid production in Synechococcus 7942. Salt concentration of 500 mM induced a five-and threefold increase in the production of carbohydrates and lipids, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…sodium (Na + ) and chloride (Cl − ), and deficiency of mineral elements (Isayenkov and Maathuis, 2019). Additionally, salinity leads to oxidative stress in plants because of overaccumulation of reactive oxygen species (Verma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…sodium (Na + ) and chloride (Cl − ), and deficiency of mineral elements (Isayenkov and Maathuis, 2019). Additionally, salinity leads to oxidative stress in plants because of overaccumulation of reactive oxygen species (Verma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the percentage of C16:1 in strain JY13 with salt stress was 28.5% lower than that in strain JY00 with salt stress; the percentage of C18:1 in strain JY13 with salt stress was 1.53-fold higher than that in strain JY00 with salt stress. A previous study also showed that the content of C16:1 had significantly decreased by 29.1%, meanwhile, C18:1 increased ∼2-fold under 0.5 M NaCl conditions in S. elongatus PCC 7942 (Verma et al, 2018). However, the mechanism of conversion between C18:1 and C16:1 under salt stress is still unclear and further research should be performed in the near future.…”
Section: Comparative Targeted Metabolomics Analysis Of Strains Jy13 and Jy00mentioning
confidence: 92%
“…In addition, the carbohydrate content of strain JY13 under salt stress was 10.2% higher than that of strain JY00 under salt stress, consistent with the changes of sucrose and glycogen detected by metabolomics analysis. Previous study revealed that the contents of carbohydrates increased ∼5-fold in S. elongates PCC 7942 under 0.5 M NaCl conditions compared to control (Verma et al, 2018). Thus, it's reasonable to suppose that the increased carbohydrates contents might be used as an adaptive strategy of cyanobacteria under saline conditions.…”
Section: Comparative Targeted Metabolomics Analysis Of Strains Jy13 and Jy00mentioning
confidence: 94%
“…The cyanobacterium Synechococcus sp. 95 and some strains of Chlorella, [96][97][98] Chlorococcum 97 and Chlamydomonas. 105 It is important to note that in many studies with freshwater species, growth was severely restricted by the increased salinity, a fact that indirectly influenced lipid accumulation.…”
Section: Theinter Ac Tingeffec Tof Salinit Yandculturecond Iti On Son Lipidcontentinmi Croalg Aementioning
confidence: 99%